Relationship between clinical severity and hemodynamic impact of great saphenous vein incompetence using strain gauge plethysmography and duplex ultrasound. (September 2022) - Nelzén, P Oskar E; Skoog, Johan; Zachrisson, Helene
Objectives: To evaluate the relation of quantitative Duplex ultrasound (DUS) and strain gauge plethysmography (SGP) parameters with clinical severity and quality of life in patients with superficial venous incompetence. Methods: DUS volume flow and distal SGP refilling times (T50 and T90 ) were evaluated in 152 patients (164 Limbs) with superficial incompetence. Clinical severity and quality of life were evaluated with C of the CEAP classification, venous clinical severity score (VCSS), Aberdeen varicose vein questionnaire (AVVQ), and EuroQol 5D-3L. Results: Higher DUS volume flow was associated with higher C in CEAP scores. Volume flow was also related to T50 and T90 . Shorter T50 and T90 were associated with higher C in CEAP and VCSS. T50 was also associated with EQ-5DVAS. Reflux extension to the foot wase associated with shorter T50 and T90 and higher DUS volume flow. Conclusions: DUS volume flow and SGP refilling times are related with clinical severity and provide quantitative information regarding venous function in patients with superficial incompetence.